2011
DOI: 10.4103/2230-8229.83371
|View full text |Cite
|
Sign up to set email alerts
|

Toward smoke-free homes: A community-based study on initiatives of rural Indian women

Abstract: Context:Since the home is the primary source of exposure of children to second-hand smoke (SHS), measures to restrict smoking at home should be introduced to protect children from its adverse health consequences.Aims:Objectives of the study were to assess the level of awareness of rural Indian women on the health impacts of SHS on children and to look into the strategies they used to reduce children's exposure to SHS at home.Materials and Methods:A community-based cross-sectional study was conducted among 438 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…This finding aligns with previous studies which have shown that rural populations support smoking as a traditional, popular behavior, as well as a leisure activity [49,50]. Moreover, low educational level and lack of information on health-related hazards due to smoking were also associated with less practical activities to personally quit smoking or prevent others from smoking [51][52][53][54]. These results also suggest that women at an earlier gestation period had less knowledge about the harms from SHS, highlighting the need to educate pregnant women earlier during their pregnancy.…”
Section: Discussionsupporting
confidence: 90%
“…This finding aligns with previous studies which have shown that rural populations support smoking as a traditional, popular behavior, as well as a leisure activity [49,50]. Moreover, low educational level and lack of information on health-related hazards due to smoking were also associated with less practical activities to personally quit smoking or prevent others from smoking [51][52][53][54]. These results also suggest that women at an earlier gestation period had less knowledge about the harms from SHS, highlighting the need to educate pregnant women earlier during their pregnancy.…”
Section: Discussionsupporting
confidence: 90%
“…This is in contrast to a study among rural women in India, wherein the majority of women (75.8%) were aware about some health hazards of smokeless tobacco use on children. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Eminent knowledge of the effects of SHS is important as people are aware of the harmful effects of SHS exposure, but the extent of damage that SHS can make is unknown to people. 21 Furthermore, the knowledge of the harmful effect of SHS exposure should include the ill effect on pregnant women, fetal outcomes and the children at home. The results give further evidence to initiate specific interventions to reduce SHS exposure at home.…”
Section: Discussionmentioning
confidence: 99%